2008
DOI: 10.1007/s10897-008-9151-6
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Teens Living in the Shadow of Huntington Disease

Abstract: Research on families with Huntington Disease (HD) has primarily focused on adult decision-making surrounding predictive genetic testing and caregiver stress. Little is known about the experiences of teens living in these families. This qualitative study explored the experiences of 32 teens living in families with HD. Six focus groups were conducted across the U.S. and Canada. Data were analyzed using descriptive qualitative analysis. HD appeared to cast a shadow over the experiences described by teens. Four th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 29 publications
5
50
0
Order By: Relevance
“…The design of the larger study is reported in more detail elsewhere (Sparbel et al, 2008; Williams & Ayres, 2007; Williams et al, 2007; Williams et al, 2008). In brief, the larger study was a two phase mixed methods study in which the conduct of focus groups and development of a family concerns and strategies survey were completed in the first phase, and the survey was distributed and analyzed in the second phase.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The design of the larger study is reported in more detail elsewhere (Sparbel et al, 2008; Williams & Ayres, 2007; Williams et al, 2007; Williams et al, 2008). In brief, the larger study was a two phase mixed methods study in which the conduct of focus groups and development of a family concerns and strategies survey were completed in the first phase, and the survey was distributed and analyzed in the second phase.…”
Section: Methodsmentioning
confidence: 99%
“…Teens in the focus groups had not met each other before the focus group meetings. Additional sample details are noted elsewhere (Sparbel et al, 2008). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They sometimes have an adult role, could be expected to provide care for the parent [12] and could feel responsible for the family's functioning [13]. A recent survey showed that 7% of the 2424 responding adolescents in Sweden were involved in extensive care of a person close to them [14].…”
Section: Introductionmentioning
confidence: 99%